Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
[tex]=5x^{2} +2x-4-(2x^{2} +6x-6)\\=5x^{2} +2x-4-2x^{2} -6x+6\\=5x^{2} -2x^{2} +2x-6x-4+6\\=3x^{2} -4x+2[/tex]
Step-by-step explanation:
Hence,5x²+2x-4 and 2x²+6x-6 are the two polynomials.
To create them:
Let,5x²+2x-4 be the first polynomial and x be the another
Now, we have,
→5x²+2x-4-x=3x²-4x+2
→5x²+2x-4-(3x²-4x+2)=x
→5x²+2x-4-3x²+4x-2=x
→x=3x²-4x+2
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.